Words, Words, Words: An insider's reflections on BBC broadcasting about English. (12th August 2015) - Elmes, Simon
Abstract : It's difficult to imagine the relatively civilised, slightly worn corridors of London's old Broadcasting House, headquarters of the BBC, as being the frontline in a war. No trenches; no barbed wire; not a sign of battle-fatigue to be seen … Yet here whizz-bangs are almost as frequent as they were at the Somme. For frontline this indeed is; a place where battle-royal is pitched between the opposing camps of linguistic orthodoxy and originality. The spot where, like a pair of weirdly-named opponents from Gulliver's Travels, the Descriptivists do battle with the Prescriptivists.